Adaptive and intelligent systems Second International Conference, ICAIS 2011, Klagenfurt, Austria, September 6-8, 2011. proceedings - International Conference on Adaptive and Intelligent Systems Klagenfurt, Austria) (2009; Bouchachia, Abdelhamid; IEEE Computer Society; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the International Conference on Adaptive and Intelligent Systems, ICAIS 2011, held in Klagenfurt, Austria, in September 2011. The 36 full papers included in these proceedings together with the abstracts of 4 invited talks, were carefully reviewed and selected from 72 submissions. The contributions are organized under the following topical sections: incremental learning; adaptive system architecture; intelligent system engineering; data mining and pattern recognition; intelligent agents; and computational intelligence.
Electronic reproduction.
Keywords: Adaptive control systems -- Congresses; Expert systems (Computer science) -- Congresses; Artificial intelligence -- Congresses